Methods, Theories, and Empirical Applications in the Social Sciences - Salzborn, Samuel; Davidov, Eldad; Reinecke, Jost.; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2012)
The volume addresses major features in empirical social research from methodological and theoretical perspectives. Prominent researchers discuss central problems in empirical social research in a theory-driven way from political science, sociological or social-psychological points of view. These contributions focus on a renewed discussion of foundations together with innovative and open research questions or interdisciplinary research perspectives.
Theoretical Reflections -- Methodological development -- Theory-Driven Empirical Studies.
Keywords: Social sciences; Social Sciences; Social Sciences, general; Electronic books